Introduction to contemporary social theory - Elliott, Anthony (Routledge, 2014)
In this comprehensive, stylish and accessible introduction to contemporary social theory, Anthony Elliott and Charles Lemert examine the major theoretical traditions from the Frankfurt School to globalization and beyond. When first published, the book's wide range set new standards for introductory textbooks - social theorists discussed include Theodor Adorno, Herbert Marcuse, Michel Foucault, Jacques Lacan, Jacques Derrida, Anthony Giddens, Pierre Bourdieu, Julia Kristeva, Jurgen Habermas, Judith Butler, Slavoj Zizek, Manuel Castells, Ulrich Beck, Zygmunt Bauman, Giorgio Agamben and Manuel De Landa. Extensively developed to take into account significant recent developments in American social theory, the book offers chapters on American pragmatism, structural functionalism, ethnomethodology, black feminist thought and world-systems theory. American traditions of social theory are brought powerfully to life in treatments of intellectuals ranging from William James to Robert K. Merton, David Riesman to Randall Collins, and Patricia Hill Collins to Saskia Sassen. Introduction to Contemporary Social Theory combines lively exposition and clarity with reflective social critique and original insights, and is a superb textbook with which to navigate the twists and turns of contemporary social theory as taught in the disciplines of sociology, politics, history, cultural studies and many more.